Peran Ganda Janda dalam Menjalankan Fungsi Keluarga di Desa Unte Mungkur III Kecamatan Kolang Kabupaten Tapanuli Tengah - Yesika Paulina Purba; Roida Lumbantobing; Elvri Teresia Simbolon; Mery Silalahi; Rusmauli Simbolon (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research aims to determine the dual role of widows in carrying out family functions in Unte Mungkur III Village, Kolang District, Central Tapanuli Regency. This research uses qualitative research with a descriptive type in the form of written and spoken words from people and observed behavior. The aim of the research is to understand in depth the conditions regarding the role of widows in carrying out family functions. The data collection techniques used were observation, interviews and documentation. Apart from secondary data obtained from reading sources, researchers also use direct data obtained directly from the research object. The results of this research show that the role played by a widow is carrying out her life within the family as well as carrying out family functions and taking full responsibility for her children. It can be seen that there is a shift in a family because of the dual roles played by a woman, in general women are more focused on household matters and taking care of children. However, there is a dual role of a widow who has to work every day for the survival of the family, both in earning a living and taking care of children. Researchers found that there are 7 family functions carried out by widowed women in Unte Mungkur III Village, namely: religious function, socio-cultural function, love and affection function, protection function, socialization and education function, economic function and environmental development function.